2022
DOI: 10.1016/j.jceh.2021.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer Cell Hyaline Globules in Children With Autoimmune Hepatitis

Abstract: Background: Hyaline globules (HGs) in the cytoplasm of Kupffer cells (KCs) have been appraised for being a typical feature of autoimmune hepatitis (AIH). This study aimed to determine how useful Kupffer cell hyaline globules (KCHGs) are in diagnosing AIH vs. other causes of pediatric chronic liver diseases (PCLDs). Materials and methods: This retrospective study recruited 124 children; 58 with AIH, 50 with chronic hepatitis C virus (HCV) infection, and 16 with Wilson's disease (WD). Two pathologists retrieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(33 reference statements)
0
4
0
1
Order By: Relevance
“…The presence of hyaline globules in Kupffer cells has been suggested to serve as a diagnostic clue for AIH, and a modification of the 2008 IAIHG histology component has been proposed by Gurung et al, which requires the presence of Kupffer cell hyaline globules in addition to a prominent plasmacytic infiltration to qualify as a “typical” AIH [ 23 ]. However, this needs further validation; a few other studies demonstrated that this feature was not correlated with serum IgG levels, autoantibody status or histological activity/fibrosis, and moreover, its identification requires additional stains such as periodic acid-Schiff post-diastase (D-PAS) stain and CD68 [ 24 , 25 ]. Another interesting finding which requires further validation is the higher number of apoptotic lymphocytes in portal tractsin AIH compared to other liver diseases [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of hyaline globules in Kupffer cells has been suggested to serve as a diagnostic clue for AIH, and a modification of the 2008 IAIHG histology component has been proposed by Gurung et al, which requires the presence of Kupffer cell hyaline globules in addition to a prominent plasmacytic infiltration to qualify as a “typical” AIH [ 23 ]. However, this needs further validation; a few other studies demonstrated that this feature was not correlated with serum IgG levels, autoantibody status or histological activity/fibrosis, and moreover, its identification requires additional stains such as periodic acid-Schiff post-diastase (D-PAS) stain and CD68 [ 24 , 25 ]. Another interesting finding which requires further validation is the higher number of apoptotic lymphocytes in portal tractsin AIH compared to other liver diseases [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…23 However, this needs further validation; a few other studies demonstrated that this feature was not correlated with serum IgG levels, autoantibody status or histological activity/fibrosis, and moreover, its identification requires additional stains such as periodic acid-Schiff post-diastase (D-PAS) stain and CD68. 24,25 Another interesting finding which requires further validation is the higher number of apoptotic lymphocytes in portal tracts in AIH compared to other liver diseases. 26 The limitations of this study are as follows.…”
Section: Authors' Contributionmentioning
confidence: 99%
“…Bir çalışmada, karaciğer Kupffer hücrelerinde hiyalin globulin görülmesinin OİH'li hastaları diğer pediatrik kronik karaciğer hastalıklarından ve seropozitif OİH'yi seronegatiflerden ayırmada temel gösterge olabileceği belirtilmiştir. 21 Otoantikorlar dışında da tanıda kullanılabilecek patoloji bulgularının değerli olduğu söylenebilir.…”
Section: Discussionunclassified
“…Immune cell driven inflammation is a central mechanism in the development and progression of AIH, and targeting this inflammation with immunosuppressive therapies is an effective treatment. Among the few reports discussing the role of KCs in AIH, most focused on the finding of hyaline droplets in the cytoplasm of these cells ( 167 , 168 ). In adults this histological feature was shared between samples with AIH and primary biliary cholangitis (PBC).…”
Section: Lung Resident Macrophages In Homeostasis and Inflammationmentioning
confidence: 99%